Fifth annual report - Mew, E. B. ; Miller, Mary F. ; Norman, E. M. ; Roberts, D. ; Galbraith, H. ; Worden, M. ; Daukes, A. ; Waterworth, E. M. ; Mottram, D. B.; Capener, Norman (1932)
1932 1932 1930s 86 pages : illustrations £ s. d. Order of Oddfellows, Manchester 1 1 0 Pike & Co., Messrs. 5 0 0 St. Marks Church, Collection at 2 2 0 Starcross Girl Guides and Brownies 2 2 0 Tipton St. John Women's Institute 1 1 0 Tiverton District Collection (part), per Hon. Mrs. Butler 26 5 0 Topsham Consol. Charities 2 2 0 Torrington Girl Guides 1 10 6 Totnes Girl Guides 2 3 0 Tozer, E., Esq. (per) 2 2 0 Amounts of £1 and under 13 17 0 Total £131 2 6 SCHOOLS COT FUND, 1932. £ s. d. Colaton Raleigh School 5 0 Do. (2nd donation) 5 0 Egerton House School (5th donation) 3 0 0 Episcopal Modem School (7th donation) 14 0 Queen Elizabeth School Crediton (4th donation) 30 9 3 St. Margaret's School Old Girls 5 5 0 Tinfoil, Sale of 5 8 1 45 6 4 Amount previously acknowledged 416 18 4 Total £462 4 8 ENTERTAINMENTS, 1932. £ s. d. Chagford Carnival, per V. J. Yardley, Esq. 4 0 0 Chagford Carnival 5 0 0 Cheriton Fitzpaine Carnival 1 0 0 Chudleigh Knighton Women's Institute Whist Drive) 1 16 6 Chudleigh Carnival, per E. H. Holmes, Esq. 5 0 0 Exbourne Fete 1 1 0 Exeter Giri Guides, 10th 2 7 0 Exton, Dance, per Mrs. J. Challice 5 0 0 Newton Abbot Girl Guides, 1st 12 0 0 Okehampton, Stall at Bazaar, Surplus Goods 3 0 0 Reed, Mrs., Proceeds of Dance 5 1 0 Rotary Club of Exeter, 1926 Bazaar Balance 19 1 0 Topsham Amateur Dramatic Society 1 1 0 Topsham Rangers and Guides 16 2 9 Topsham Carnival 5 19 5 Uffculme Carnival 29 13 5 Vicary, Lieut.-Col. (per) 18 10 0 Watermouth Castle, Open Garden Day (per Mrs. Penn Curzon) 10 10 0 Williams, Mrs., Draw for Canary 2 7 9 Winkleigh, Dance at, per Rev. J. R. Paramore 2 10 0 Total £151 0 10 56 292/841.51/2/2